1992
DOI: 10.1016/0014-5793(92)80502-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic aspects of ovarian superoxide dismutase isozymes during the ovulatory process in the rat

Abstract: To investigate the role of superoxide dismutasc (SOD) in the ovulatory process, SOD isoymes and their mRNAs were determined in the ovary of 22-day-old rat. After treatment with pregnant mare serum gonadotropin (PMSG) and human chorionic gonadotropin (hCG), ovarian sctivity of Mn-SOD decreased markedly while Cu/Zn-SOD remained unchanged. However, the ovarian level of mRNA for Mn-SOD markedly increased after hCG-treatment while that for Cu/Zn-SOD decreased only slightly. Ovulation WPS inhibited by intravenous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Functional ovarian damage in obese females has been associated with abnormal levels of antioxidant enzymes (Lim and Luderer, 2011), and the mammalian ovary possesses antioxidant defenses, including ROS-scavenging enzymes such as CAT, GSH-Px, and SOD (Sato et al, 1992;Hsieh et al, 1997). CAT catalyzes the decomposition of H 2 O 2 into H 2 O and O 2 to protect cells from H 2 O 2 toxicity (Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Functional ovarian damage in obese females has been associated with abnormal levels of antioxidant enzymes (Lim and Luderer, 2011), and the mammalian ovary possesses antioxidant defenses, including ROS-scavenging enzymes such as CAT, GSH-Px, and SOD (Sato et al, 1992;Hsieh et al, 1997). CAT catalyzes the decomposition of H 2 O 2 into H 2 O and O 2 to protect cells from H 2 O 2 toxicity (Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian ovaries possess antioxidant defenses including the antioxidant tripeptide glutathione (GSH), and ROS-scavenging enzymes such as SOD, GSH-Px, CAT, glutathione S-transferase (GST), and peroxiredoxin (PRDX) [ 4 , 56 , 57 ]. We hypothesized that ovarian aging is associated with decreased expression of ovarian antioxidant genes and lower antioxidant enzyme levels, resulting in oxidative damage to ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio between the levels of oxidant and antioxidant defenses changes depending on the hormonal conditions. After the gonadotropin surge (human chorionic gonadotropin (hCG) or luteinizing hormone (LH)), ROS levels increase while the expression of antioxidants decrease to enhance ovulation (Laloraya et al 1988, Sato et al 1992, Shkolnik et al 2011. Using in vivo and in vitro assays, it has been shown that antioxidants significantly reduce the LH-induced cumulus mucification/expansion, progesterone production, and activation of two signaling pathways (PKA and MAPK), all events indispensable for the ovulatory process (Shkolnik et al 2011).…”
Section: Introductionmentioning
confidence: 99%